Effect of Financial Ratios on Net Profit Growth in Manufacturing Companies in the Basic and Chemical Industry Subsectors Listed on the Indonesia Stock Exchange - Adella Viona; Maya Syaula; Noni Ardian (Yayasan Multidimensi Kreatif, 2025)
This study was conducted to find out how the influence of current ratio, debt to equity ratio, return on assets, total assets turnover and price to book value on net profit growth in manufacturing companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange. Data is taken from www.idx.co.id. Data used from 2017-2023. The research was conducted in 2024. The population in this study is 61 companies with a sample of 38 companies. This study uses quantitative data processed with the Eviews 9 application using the panel data regression method. The test results gave the conclusion that only the return on assets variable partially had a positive and significant effect on net profit growth, while the current ratio. debt to equity ratio, total assets turnover and price to book value partially did not have a significant effect on net profit growth. Simultaneously, the current ratio, debt to equity ratio, return on assets, total assets turnover and price to book value have a positive and significant effect on the growth of net profit of manufacturing companies in the basic and chemical industry sectors. The contribution given by the variables of current ratio, debt to equity ratio, return on assets, total asset turnover and price to book value to net profit growth was 26.05%, while the level of tightness of the variables current ratio, debt to equity ratio, return on assets, total assets turnover, and the price to book value to net profit growth is quite tight or strong enough.